Features of Forming a Culture of Communication Among Students - Z.A.Shaumarova; G.K.Karimova (Universitas Muhammadiyah Sidoarjo, 2022)
This article discusses the culture of communication as a means of universal communication. The article gives an idea of the components of student communication culture